PENGARUH MORDAN AIR KELAPA PADA PENCELUPAN BAHAN KATUN MENGGUNAKAN EKSTRAK UMBI TEMULAWAK (CURCUMA XANTHORRIZA ROXB) - MARTALINDA, SELVI; rahmiati, rahmiati; adriani, adriani (Journal of Home Economics and Tourism, 2013)
The purpose of this study is: to reveal the effect of the use of coconut water mordantthe color / hue, bright dark color / value, and the flatness of color produced in cottondyeing using ginger root extract (Curcuma Roxb Xanthorriza). This type of research isexperimental research. Variable X is a root of ginger (Curcuma Roxb Xanthorriza) aredyed with cotton. Variable X1 is mordant dyeing without the use of coconut water, X2is Mordant dyeing using coconut water. As well as the Y variable dye differences inresults include: Y1 different color / hue dye yield, Y2 differences bright dark color /value, and Y3 is the flatness of the color difference. Types of data used are primarydata. Sources of data in this study is 15 respondents. Mechanical analysis of dataprocessed and compiled, then analyzed using a ratio of 2 independent variables (t test).Then processed using SPSS 15. From the analysis of data on the color (hue) colorsobtained without the use of gold for dyeing mordant and mordant yellow for dyeingusing coconut water.Kata kunci: pengaruh mordan air kelapa, pencelupan bahan katun, ekstrak umbi temulawak (Curcuma Xanthorriza Roxb)